2014 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--20227
|View full text |Cite
|
Sign up to set email alerts
|

Creation of a Co-Terminal BS/MS Civil Engineering Degree Program

Abstract: Sleep received his Bachelors degree in Geological Engineering from the University of Mississippi. After working for the USACE and private consulting, Matthew returned to graduate school at Virginia Tech receiving a Masters and PhD in Civil Engineering. His research and consulting focus is in Geotechnical Engineering with and emphasis on dam and levee projects. He is currently an assistant professor of Civil Engineering at Oregon Institute of Technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…However, it is unclear that any such programs exist. Riley et al [39] reported in 2014 that 37 ABET-accredited programs offered a civil engineering BS combined with an MS in some manner (such as co-terminal degrees). These degrees may be more popular for some specialties within civil engineering.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unclear that any such programs exist. Riley et al [39] reported in 2014 that 37 ABET-accredited programs offered a civil engineering BS combined with an MS in some manner (such as co-terminal degrees). These degrees may be more popular for some specialties within civil engineering.…”
Section: Introductionmentioning
confidence: 99%